Preparation method and application of graphene / cellulose hybrid composite aerogel blocking material

Through the preparation of graphene/cellulose hybrid composite aerogel, the problems of oil-based drilling leak plugging materials in leak plugging properties and stability are solved, and efficient sealing and bearing of shale gas horizontal well walls is achieved. The improvement of pressure capacity ensures the stability of the well wall during drilling.

CN119286044APending Publication Date: 2025-01-10SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411401873.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing oil-based drilling leak plugging materials have problems in the nature of leak plugging agent, leak plugging capacity while drilling, and the stability of leak plugging materials, resulting in low leakage plugging success rate and insufficient pressure bearing capacity, and cannot effectively prevent shale gas horizontal wells. The well wall collapsed.

Method used

The preparation method of graphene/cellulose hybrid composite aerogel sealing material is adopted to form a porous, oil-absorbing flexible aerogel by combining graphene oxide with hydroxypropyl methyl cellulose, polyvinyl alcohol and polyacrylamide. Using hydrogen bond interaction and fiber network structure, mechanical strength and flexibility are improved to form an efficient blocking network.

Benefits of technology

It realizes effective sealing of micro-mm-scale cracks, improves the pressure bearing capacity of the well wall, reduces the formation collapse pressure, expands the safety density window of drilling fluid, and the materials are easy to assemble, environmentally friendly and easy to mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286044A_ABST
    Figure CN119286044A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of plugging materials, in particular to a preparation method and application of a graphene / cellulose hybrid composite aerogel plugging material.The preparation method comprises the following steps that A, graphene oxide dispersion liquid is prepared and heated and stirred to adjust the pH value to 4.5-8.5; b, sequentially adding hydroxypropyl methyl cellulose, polyvinyl alcohol, polyacrylamide and a sodium borate solution into the graphene oxide dispersion liquid treated in the step A at intervals to obtain a modified graphene dispersion liquid; and C, heating, preserving heat and dialyzing the modified graphene dispersion liquid obtained in the step B, repeating freezing and unfreezing for at least two times after dialyzing, performing freeze drying, and performing thermal annealing treatment in an inert atmosphere to obtain the graphene / cellulose hybrid composite aerogel plugging material. The dense holes in the surface and the interior of the composite aerogel plugging material are beneficial to absorption of oil to form a more compact plugging network structure layer, a good filling and covering effect on cracks is achieved, and the cracks are effectively plugged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plugging materials, and in particular to a preparation method and application of a graphene / cellulose hybrid composite aerogel plugging material. Background Art

[0002] At present, in order to prevent the wellbore collapse of shale gas horizontal wells, oil-based drilling fluids have been widely used in domestic drilling construction. However, oil-based drilling fluids cannot solve the problem of wellbore instability very well, and the fundamental reason is the hydraulic fracturing effect. When the oil phase filtrate invades the cracks, the cracks open, and the friction of the joint surface is greatly reduced, the failure pressure rises significantly. If the filtrate cannot be effectively blocked outside the cracks, the collapse pressure cannot be prevented. Therefore, for oil-based drilling fluids, strengthening plugging, preventing filtrate from entering the micro-cracks of the formation, reducing the formation collapse pressure, improving the pressure bearing capacity of the wellbore, and expanding the safe density window of the drilling fluid are the key to shale gas horizontal well drilling.

[0003] There are some common problems with existing oil-based drilling plugging materials. First, the success rate of one-time plugging is low, which may be because the properties of the plugging agent are relatively simple and it is difficult to form a stable pressure-bearing plugging layer on the smooth fracture wall, resulting in low pressure-bearing capacity. Secondly, the current while-drilling plugging technology mainly uses solid particles of different particle sizes for bridging plugging. However, these particle sizes are often difficult to fully match the leakage holes and seams, and effective while-drilling plugging cannot be achieved. In addition, the plugging zone formed by the plugging material is easily diluted by the formation fluid, or the structure loosens when the pressure is excited, resulting in plugging failure.

[0004] In summary, existing oil-based drilling plugging materials have certain problems in plugging agent properties, plugging while drilling capability, and plugging material stability. In order to solve these problems, it is necessary to continuously improve and optimize plugging materials and technologies, improve plugging success rate and pressure bearing capacity, and meet the needs of drilling safety and exploration and development. Summary of the invention

[0005] In order to solve the above technical problems, an embodiment of the present invention provides a preparation method and application of a graphene / cellulose hybrid composite aerogel plugging material.

[0006] To achieve the above object, the embodiments of the present invention adopt the following technical solutions:

[0007] The present invention provides a method for preparing a graphene / cellulose hybrid composite aerogel plugging material, comprising the following steps:

[0008] A. preparing graphene oxide powder into a graphene oxide dispersion, and heating and stirring to adjust the pH value to 4.5-8.5;

[0009] B. Adding hydroxypropyl methylcellulose, polyvinyl alcohol, polyacrylamide and sodium borate solution to the graphene oxide dispersion treated in step A in sequence and at intervals to obtain a modified graphene dispersion;

[0010] C. The modified graphene dispersion obtained in step B is heated, kept warm and dialyzed, and after the dialyzation, the dispersion is frozen and thawed at least twice, and then freeze-dried, and then thermally annealed in an inert atmosphere to obtain a graphene / cellulose hybrid composite aerogel plugging material.

[0011] In some embodiments, in step A, the graphene oxide dispersion is prepared by the following method: dissolving graphene oxide powder in deionized water and performing ultrasonic dispersion to obtain a graphene oxide dispersion, and the heating temperature is 70°C to 130°C.

[0012] In some embodiments, in step A, the concentration of the graphene oxide dispersion is 5 mg / mL to 15 mg / mL.

[0013] In some embodiments, in step B, the mass ratio of the hydroxypropyl methylcellulose to the graphene oxide powder in step A is 1:(0.5-1.5), the mass ratio of the hydroxypropyl methylcellulose and polyvinyl alcohol is (1.3-3.1):1, the mass ratio of the hydroxypropyl methylcellulose to polyacrylamide is (3-7):1, the mass fraction of the sodium borate solution is 1.5%-4.5%, and the mass volume ratio of the hydroxypropyl methylcellulose to the sodium borate solution is 1g / 1mL.

[0014] In some embodiments, in step C, the heating temperature is 120° C. to 200° C., and the insulation time is 6 h to 12 h.

[0015] In some embodiments, in step C, the dialysis time is 8 h to 14 h.

[0016] In some embodiments, in step C, the freeze-drying time is 24 hours to 48 hours, the temperature is -30°C to -60°C, and the vacuum degree is 1Pa to 25Pa.

[0017] In some embodiments, in step C, the thermal annealing treatment time is 0.1h~1h, the thermal annealing treatment temperature is 10℃~240℃, the heating rate is 1℃ / min~10℃ / min, the inert atmosphere is argon, and the argon intake rate is 5mL / min~20mL / min.

[0018] Compared with the prior art, the present invention has at least the following beneficial effects:

[0019] The porous, oil-absorbing flexible graphene / cellulose hybrid composite aerogel plugging material prepared by the present invention has good plugging properties for micro-millimeter-scale cracks, and its own flexibility is a prominent feature compared to other composite aerogels;

[0020] Graphene / cellulose hybrid materials are prepared through hydrogen bond interactions. Hydrogen bonds are directional and saturated. Usually, each hydrogen atom can only combine with two adjacent atoms with high electronegativity, and there is a charge transfer phenomenon. There are many hydroxyl groups on the surface of cellulose. When the cellulose dispersion is mixed with graphene oxide, the hydrogen atoms on the cellulose hydroxyl groups and the electronegative oxygen atoms of graphene oxide combine to form hydrogen bonds. And because both graphene oxide and cellulose have high specific surface areas, more hydrogen bond interactions are formed between the two, which promotes the combination and hybridization of the two at the nanoscale, making the aerogel have better mechanical strength and flexibility.

[0021] The introduction of polyacrylamide effectively weakens the agglomeration and accumulation between graphene sheets, and the introduction of polyvinyl alcohol brings good flexibility to the aerogel. The prepared porous, oil-absorbing flexible graphene / cellulose hybrid composite aerogel has dense pores on the surface and inside, which is conducive to the absorption of oil and forms a denser plugging network structure layer, which plays a good filling and covering role on cracks. It has a good absorption effect on oil in both acidic and alkaline environments, and the flexibility is further improved after oil absorption.

[0022] The porous, oil-absorbing flexible graphene / cellulose hybrid composite aerogel of the present invention has a particle size of 100 μm to 400 μm and can be ground by a planetary ball mill. Due to the high degree of cross-linking of graphene oxide and cellulose, the formed three-dimensional network structure has a low swelling rate and significant micro-millimeter characteristics, thereby being able to efficiently seal the micro-millimeter pores and cracks of rocks.

[0023] Combining gel technology with drilling fluid technology, the fiber network can play a role in strengthening the structure on the graphene multilayer stacking network layer. When external stress is applied to the surface of the hybrid composite aerogel, the fiber network can achieve a certain buffering effect and prevent the further expansion of the cracks, so that the composite aerogel can meet certain mechanical requirements. The hybrid composite aerogel material can improve its plugging effect as a plugging agent. The hybrid composite aerogel plugging particles enter the cracks to form an inner partition wall, effectively plugging the cracks, preventing the drilling fluid filtrate from penetrating into the micro-cracks of the shale wellbore, blocking the contact between the drilling fluid filtrate and the formation, reducing the formation collapse pressure, improving the pressure bearing capacity of the wellbore, and expanding the safe density window of the drilling fluid. In the shale formation containing a large number of micro-millimeter-level microcracks, the effective plugging of micro-millimeter pores is the key to the stability of the wellbore. Therefore, the composite aerogel material helps to ensure the well sealing mechanism and wellbore instability during the drilling process. Through cross-linking and lipophilic strengthening, the defects of traditional cellulose aerogels are effectively improved. Combined with the excellent properties of graphene, the mechanical strength is improved so that it can maintain a certain flexibility after absorbing oil and cope with the threats posed by micro-millimeter cracks during the drilling process.

[0024] Graphene oxide and cellulose, the main raw materials for the preparation of this plugging material, are easy to assemble and functionalize. They are currently in industrial mass production. The raw materials are easily available, non-toxic, economical and cheap, and do not produce toxic substances and gases when reacting with the above-mentioned reagents. The porous, oil-absorbing flexible graphene / cellulose hybrid composite aerogel prepared by a series of cross-linking methods and pore-forming technologies is easy to operate, the preparation process is not complicated, it is easy to mass produce and is harmless to the environment, thus constructing an environmentally friendly drilling fluid system. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1a This is a schematic diagram of the porous structure of the graphene / cellulose hybrid composite aerogel plugging material according to Example 1 of the present invention;

[0026] Figure 1b This is a physical picture of the graphene / cellulose hybrid composite aerogel plugging material of Example 1 of the present invention;

[0027] Figure 2a This is a scanning electron microscope image (50 μm) of the outer surface of the graphene / cellulose hybrid composite aerogel plugging material of Example 2 of the present invention;

[0028] Figure 2b This is a scanning electron microscope image (5 μm) of the outer surface of the graphene / cellulose hybrid composite aerogel plugging material of Example 2 of the present invention;

[0029] Figure 2c This is a scanning electron microscope image (50 μm) of the cross section of the graphene / cellulose hybrid composite aerogel plugging material of Example 2 of the present invention;

[0030] Figure 2d This is a scanning electron microscope image (5 μm) of the cross section of the graphene / cellulose hybrid composite aerogel plugging material of Example 2 of the present invention;

[0031] Figure 3 This is a schematic diagram of the change in contact angle within 0.2s of dropping the graphene / cellulose hybrid composite aerogel plugging material of Example 3 of the present invention using white oil as the medium;

[0032] Figure 4 It is a columnar schematic diagram of the oil absorption rate when the graphene / cellulose hybrid composite aerogel plugging materials of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Example 2 of the present invention reach adsorption equilibrium. DETAILED DESCRIPTION

[0033] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in some embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.

[0034] Example 1

[0035] 1) Dissolve 0.5 g of graphene oxide powder in 100 mL of deionized water, stir with a glass rod to dissolve, then move to an ultrasonic disperser at room temperature, set the ultrasonic time of the ultrasonic disperser to 20 min, the power to 400 w, the single ultrasonic time to 1 s, the single interval time to 0.5 s, and the frequency to 20 Hz, transfer the ultrasonicated graphene oxide dispersion to an oil bath for heating, the heating time is 6 min, the heating temperature is 70 ° C, the stirring rate is 1400 rpm / min, and the pH value is adjusted to 6.5;

[0036] 2) Add 1 g of hydroxypropyl methylcellulose to the graphene oxide dispersion that is being stirred and heated at a uniform speed, add 0.33 g of polyvinyl alcohol after an interval of 3 minutes, add 0.143 g of polyacrylamide after an interval of 2 minutes, and at the same time add 1 mL of 4.5 wt% sodium borate solution, keep for 1.2 hours, and obtain a preliminary modified graphene dispersion, then transfer the dispersion to a polytetrafluoroethylene liner, increase the roller furnace temperature to 160°C, and continue for 6 hours;

[0037] 3) After the graphene / cellulose modified dispersion is heated in the roller furnace, it is taken out from the polytetrafluoroethylene liner, cooled, and then ultrasonically dispersed for 30 minutes. The ultrasonic graphene / cellulose dispersion is then placed in a dialysis bag and dialyzed in a 1.5% mass fraction ethanol solution for 8 hours.

[0038] 4) Freezing the dialyzed graphene / cellulose modified dispersion at -20°C for 8 hours, thawing it after freezing, and then freezing it again, repeating the thawing-freezing operation once, and the second freezing time is the same as the first freezing time;

[0039] 5) placing the frozen solid of the graphene / cellulose modified dispersion liquid that has been thawed and frozen into a freeze dryer for drying, wherein the freezing temperature is set to -60°C, the vacuum degree is set to 20Pa after evacuation, and the freeze drying time is 24 hours. After the freeze drying is completed, a semi-finished low-density porous, oil-absorbing, and highly elastic graphene / cellulose composite aerogel is obtained;

[0040] 6) placing the obtained freeze-dried aerogel for thermal annealing in an inert atmosphere, wherein the thermal annealing time is 0.5 h, the thermal annealing temperature is 30° C., the heating rate is 1° C. / min, the inert atmosphere is argon, and the argon intake rate is 20 mL / min. After the annealing treatment is completed, the aerogel is taken out and then cooled to room temperature to obtain a finished low-density porous, oil-absorbing and highly elastic graphene / cellulose composite aerogel.

[0041] Example 2

[0042] 1) Dissolve 1.0 g of graphene oxide powder in 100 mL of deionized water, stir with a glass rod to dissolve, then move to an ultrasonic disperser at room temperature, set the ultrasonic time of the ultrasonic disperser to 20 min, the power to 400 w, the single ultrasonic time to 1 s, the single interval time to 0.5 s, and the frequency to 20 Hz, transfer the ultrasonicated graphene oxide dispersion to an oil bath for heating, the heating time is 18 min, the heating temperature is 90 ° C, the stirring rate is 1400 rpm / min, and the pH is adjusted to 7;

[0043] 2) Add 1 g of hydroxypropyl methylcellulose to the graphene oxide dispersion that is being stirred and heated at a uniform speed, add 0.5 g of polyvinyl alcohol after an interval of 3 minutes, add 0.2 g of polyacrylamide after an interval of 2 minutes, and at the same time add 1 mL of 3 wt% sodium borate solution, keep for 1.0 h, and obtain a preliminary modified graphene dispersion, then transfer the dispersion to a polytetrafluoroethylene liner, increase the roller furnace temperature to 120° C., and continue for 8 h;

[0044] 3) After the graphene / cellulose modified dispersion is heated in the roller furnace, it is taken out from the polytetrafluoroethylene liner, cooled, and then ultrasonically dispersed for 30 minutes. The ultrasonic graphene / cellulose dispersion is then placed in a dialysis bag and dialyzed in a 1.5% mass fraction ethanol solution for 8 hours.

[0045] 4) The dialyzed graphene / cellulose modified dispersion was quickly frozen in liquid nitrogen for 2 minutes. After the freezing was completed, it was thawed and then frozen again. The thawing-freezing operation was repeated twice, and the second freezing time was the same as the first freezing time;

[0046] 5) placing the frozen solid of the graphene / cellulose modified dispersion liquid that has been thawed and frozen into a freeze dryer for drying, wherein the freezing temperature is set to -50°C, the vacuum degree is set to 20Pa after evacuation, and the freeze drying time is 30 hours. After the freeze drying is completed, a semi-finished low-density porous, oil-absorbing, and highly elastic graphene / cellulose composite aerogel is obtained;

[0047] 6) placing the obtained freeze-dried aerogel for thermal annealing in an inert atmosphere, wherein the thermal annealing time is 0.4 h, the thermal annealing temperature is 60° C., the heating rate is 5° C. / min, the inert atmosphere is argon, and the argon intake rate is 20 mL / min. After the annealing treatment is completed, the aerogel is taken out and then cooled to room temperature to obtain a finished low-density porous, oil-absorbing and highly elastic graphene / cellulose composite aerogel.

[0048] Example 3

[0049] 1) Dissolve 1.5 g of graphene oxide powder in 100 mL of deionized water, stir with a glass rod to dissolve, then move to an ultrasonic disperser at room temperature, set the ultrasonic time of the ultrasonic disperser to 20 min, the power to 400 w, the single ultrasonic time to 1 s, the single interval time to 0.5 s, and the frequency to 20 Hz, transfer the ultrasonicated graphene oxide dispersion to an oil bath for heating, the heating time is 24 min, the heating temperature is 120 ° C, the stirring rate is 1400 rpm / min, and the pH value is adjusted to 8.5;

[0050] 2) Add 1 g of hydroxypropyl methylcellulose to the graphene oxide dispersion that is being stirred and heated at a uniform speed, add 0.6 g of polyvinyl alcohol after an interval of 3 minutes, add 0.2 g of polyacrylamide after an interval of 2 minutes, and at the same time add 1 mL of 3.0 wt% sodium borate solution, keep for 0.5 h, and obtain a preliminary modified graphene dispersion, then transfer the dispersion to a polytetrafluoroethylene liner, increase the roller furnace temperature to 100 ° C, and continue for 10 h;

[0051] 3) After the graphene / cellulose modified dispersion is heated in the roller furnace, it is taken out from the polytetrafluoroethylene liner, cooled, and then ultrasonically dispersed for 30 minutes. The ultrasonic graphene / cellulose dispersion is then placed in a dialysis bag and dialyzed in a 1.5% mass fraction ethanol solution for 8 hours;

[0052] 4) The dialyzed graphene / cellulose modified dispersion was frozen on a liquid nitrogen ice plate for 2 minutes. After the freezing was completed, it was thawed and then frozen again. The thawing-freezing operation was repeated 3 times, and the second freezing time was the same as the first freezing time.

[0053] 5) placing the frozen solid of the graphene / cellulose modified dispersion liquid that has been thawed and frozen into a freeze dryer for drying, wherein the freezing temperature is set to -45°C, the vacuum degree is set to 18 Pa after evacuation, and the freeze drying time is 48 hours. After the freeze drying is completed, a semi-finished low-density porous, oil-absorbing, and highly elastic graphene / cellulose composite aerogel is obtained;

[0054] 6) placing the obtained freeze-dried aerogel for thermal annealing in an inert atmosphere, wherein the thermal annealing time is 0.2 h, the thermal annealing temperature is 30° C., the heating rate is 5° C. / min, the inert atmosphere is argon, and the argon intake rate is 20 mL / min. After the annealing treatment is completed, the aerogel is taken out and then cooled to room temperature to obtain a finished low-density porous, oil-absorbing and highly elastic graphene / cellulose composite aerogel.

[0055] Comparative Example 1

[0056] In this comparative example 1, a graphene aerogel prepared by a hydrothermal reduction method is prepared, comprising the following steps:

[0057] 1) Dissolve 0.5 g of graphene oxide powder in 100 mL of deionized water, stir with a glass rod to dissolve, then move to an ultrasonic disperser at room temperature, set the ultrasonic time of the ultrasonic disperser to 20 min, the power to 400 w, the single ultrasonic time to 1 s, the single interval time to 0.5 s, and the frequency to 20 Hz, and take 5 mL of this suspension dispersion into a glass bottle;

[0058] 2) The graphene oxide dispersion in the glass bottle is transferred to a polytetrafluoroethylene liner, and then the polytetrafluoroethylene liner is placed in a high temperature and high pressure reactor for hydrothermal reaction at 120° C. for 12 hours to obtain a reduced graphene oxide hydrogel;

[0059] 3) placing the reduced graphene oxide hydrogel in a refrigerator at -20°C and freezing it randomly for 8 hours; freezing and drying the frozen reduced graphene oxide hydrogel in a freeze dryer (with a cold temperature of -60°C and a pressure of 18 Pa) for 48 hours to obtain reduced graphene oxide aerogel.

[0060] Comparative Example 2

[0061] In this comparative example 2, a reduced graphene oxide aerogel reduced by conventional ascorbic acid is prepared, comprising the following steps:

[0062] 1) Dissolve 0.5 g of graphene oxide powder in 100 mL of deionized water, stir with a glass rod to dissolve, then move to an ultrasonic disperser at room temperature, set the ultrasonic time of the ultrasonic disperser to 20 min, the power to 400 w, the single ultrasonic time to 1 s, the single interval time to 0.5 s, and the frequency to 20 Hz, then add 1 g of ascorbic acid, ultrasonicate the mixture for 15 min, and take 5 mL of the solution into a glass bottle;

[0063] 2) The mixed suspension dispersion in the glass bottle is transferred to a polytetrafluoroethylene liner, and then the polytetrafluoroethylene liner is placed in a high temperature and high pressure reactor for hydrothermal reaction at 120° C. for 12 hours to obtain ascorbic acid modified reduced graphene oxide hydrogel;

[0064] 3) The ascorbic acid-modified reduced graphene oxide hydrogel was dialyzed in a 1% mass fraction ethanol solution for 8 hours, and then placed in a refrigerator at -20°C for random freezing for 8 hours; the frozen sample was freeze-dried in a freeze dryer (freezing temperature of -60°C, pressure of 18 Pa) for 36 hours to obtain ascorbic acid-modified reduced graphene oxide aerogel.

[0065] Comparative Example 3

[0066] This comparative example 3 prepares a method for preparing a composite aerogel, comprising the following steps:

[0067] 1) Dissolve 0.5 g of graphene oxide powder in 100 mL of deionized water, stir with a glass rod to dissolve, then move to an ultrasonic disperser at room temperature, set the ultrasonic time of the ultrasonic disperser to 20 min, the power to 400 w, the single ultrasonic time to 1 s, the single interval time to 0.5 s, and the frequency to 20 Hz, transfer the ultrasonicated graphene oxide dispersion to an oil bath for heating, the heating time is 6 min, the heating temperature is 70 ° C, the stirring rate is 1400 rpm / min, and the pH value is adjusted to 6.5;

[0068] 2) Add 1 g of hydroxypropyl methylcellulose to the graphene oxide dispersion that is being stirred and heated at a uniform speed, add 0.33 g of polyvinyl alcohol after an interval of 3 minutes, add 0.143 g of polyacrylamide after an interval of 2 minutes, and at the same time add 1 mL of 4.5 wt% sodium borate solution, and then add 0.5 g of CuCl2 powder and keep it for 1.2 hours to obtain a preliminary modified graphene dispersion, then transfer the dispersion to a polytetrafluoroethylene liner, increase the roller furnace temperature to 160°C, and continue for 6 hours;

[0069] 3) After the graphene / cellulose modified dispersion is heated in the roller furnace, it is taken out from the polytetrafluoroethylene liner, cooled, and then ultrasonically dispersed for 30 minutes. The ultrasonic graphene / cellulose dispersion is then placed in a dialysis bag and dialyzed in a 1.5% mass fraction ethanol solution for 8 hours;

[0070] 4) The dialyzed graphene / cellulose modified dispersion is placed in a refrigerator for freezing at a temperature of -20°C for 8 hours. After the freezing is completed, it is thawed and then frozen again. The thawing-freezing operation is repeated once, and the second freezing time is the same as the first freezing time.

[0071] 5) placing the frozen solid of the graphene / cellulose modified dispersion liquid that has been thawed and frozen into a freeze dryer for drying, wherein the freezing temperature is set to -60°C, the vacuum degree is set to 20Pa after evacuation, and the freeze drying time is 24 hours. After the freeze drying is completed, a semi-finished low-density porous, oil-absorbing, and highly elastic graphene / cellulose composite aerogel is obtained;

[0072] 6) The freeze-dried aerogel is placed for thermal annealing in an inert atmosphere. The thermal annealing time is 0.5 h, the thermal annealing temperature is 30° C., the heating rate is 1° C. / min, the inert atmosphere is argon, and the argon intake rate is 20 mL / min. After the annealing treatment is completed, the aerogel is taken out and then cooled to restore to room temperature to obtain the finished composite aerogel.

[0073] Comparative Example 4

[0074] This comparative example 4 prepares a method for preparing a composite aerogel, comprising the following steps:

[0075] 1) Dissolve 0.5 g of graphene oxide powder in 100 mL of deionized water, stir with a glass rod to dissolve, then move to an ultrasonic disperser at room temperature, set the ultrasonic time of the ultrasonic disperser to 20 min, the power to 400 w, the single ultrasonic time to 1 s, the single interval time to 0.5 s, and the frequency to 20 Hz, transfer the ultrasonicated graphene oxide dispersion to an oil bath for heating, the heating time is 6 min, the heating temperature is 70 ° C, the stirring rate is 1400 rpm / min, and the pH value is adjusted to 6.5;

[0076] 2) Add 1 g of hydroxypropyl methylcellulose to the graphene oxide dispersion that is being stirred and heated at a uniform speed, add 0.33 g of polyvinyl alcohol after an interval of 3 minutes, add 0.143 g of polyacrylamide after an interval of 2 minutes, and at the same time add 1 mL of 4.5 wt% sodium borate solution, and then add 0.5 g of xanthan gum powder and keep it for 1.2 hours to obtain a preliminary modified graphene dispersion, then transfer the dispersion to a polytetrafluoroethylene liner, increase the roller furnace temperature to 160°C, and continue for 6 hours;

[0077] 3) After the graphene / cellulose modified dispersion is heated in the roller furnace, it is taken out from the polytetrafluoroethylene liner, cooled, and then ultrasonically dispersed for 30 minutes. The ultrasonic graphene / cellulose dispersion is then placed in a dialysis bag and dialyzed in a 1.5% mass fraction ethanol solution for 8 hours.

[0078] 4) Freezing the dialyzed graphene / cellulose modified dispersion at -20°C for 8 hours, thawing it after freezing, and then freezing it again, repeating the thawing-freezing operation once, and the second freezing time is the same as the first freezing time;

[0079] 5) placing the frozen solid of the graphene / cellulose modified dispersion liquid that has been thawed and frozen into a freeze dryer for drying, wherein the freezing temperature is set to -60°C, the vacuum degree is set to 20Pa after evacuation, and the freeze drying time is 24 hours. After the freeze drying is completed, a semi-finished low-density porous, oil-absorbing, and highly elastic graphene / cellulose composite aerogel is obtained;

[0080] 6) The freeze-dried aerogel is placed for thermal annealing in an inert atmosphere. The thermal annealing time is 0.5 h, the thermal annealing temperature is 30° C., the heating rate is 1° C. / min, the inert atmosphere is argon, and the argon intake rate is 20 mL / min. After the annealing treatment is completed, the aerogel is taken out and then cooled to restore to room temperature to obtain the finished composite aerogel.

[0081] Comparative Example 5

[0082] This comparative example 5 prepares a method for preparing a composite aerogel, comprising the following steps:

[0083] 1) Dissolve 0.5 g of graphene oxide powder in 100 mL of deionized water, stir with a glass rod to dissolve, then move to an ultrasonic disperser at room temperature, set the ultrasonic time of the ultrasonic disperser to 20 min, the power to 400 w, the single ultrasonic time to 1 s, the single interval time to 0.5 s, and the frequency to 20 Hz, transfer the ultrasonicated graphene oxide dispersion to an oil bath for heating, the heating time is 6 min, the heating temperature is 70 ° C, the stirring rate is 1400 rpm / min, and the pH value is adjusted to 6.5;

[0084] 2) Add 1 g of hydroxypropyl methylcellulose to the graphene oxide dispersion that is being stirred and heated at a uniform speed, add 0.33 g of polyvinyl alcohol after an interval of 3 minutes, add 0.143 g of polyacrylamide after an interval of 2 minutes, and at the same time add 1 mL of 4.5 wt% sodium borate solution, and then add 0.5 g of SiO2 powder and keep it for 1.2 hours to obtain a preliminary modified graphene dispersion, then transfer the dispersion to a polytetrafluoroethylene liner, increase the roller furnace temperature to 160°C, and continue for 6 hours;

[0085] 3) After the graphene / cellulose modified dispersion is heated in the roller furnace, it is taken out from the polytetrafluoroethylene liner, cooled, and then ultrasonically dispersed for 30 minutes. The ultrasonic graphene / cellulose dispersion is then placed in a dialysis bag and dialyzed in a 1.5% mass fraction ethanol solution for 8 hours;

[0086] 4) Freezing the dialyzed graphene / cellulose modified dispersion at a refrigerator temperature of -20°C for 8 hours. After freezing, thawing it, and then freezing it again. Repeating the thawing-freezing operation once, the second freezing time is the same as the first freezing time.

[0087] 5) placing the frozen solid of the graphene / cellulose modified dispersion liquid that has been thawed and frozen into a freeze dryer for drying, wherein the freezing temperature is set to -60°C, the vacuum degree is set to 20Pa after evacuation, and the freeze drying time is 24 hours. After the freeze drying is completed, a semi-finished low-density porous, oil-absorbing, and highly elastic graphene / cellulose composite aerogel is obtained;

[0088] 6) After the freeze-dried aerogel is placed, it is subjected to thermal annealing treatment under an inert atmosphere. The thermal annealing time is 0.5 h, the thermal annealing temperature is 30° C., the heating rate is 1° C. / min, the inert atmosphere is argon, and the argon intake rate is 20 mL / min. After the annealing treatment is completed, it is taken out and then cooled to restore to room temperature to obtain the finished composite aerogel.

[0089] Experimental example

[0090] 1. The porous, oil-absorbing flexible graphene / cellulose hybrid composite aerogel plugging material prepared in Example 1 of the present invention was bent to illustrate its flexibility, and a digital photo of its porous morphology was taken.

[0091] 2. The surface and cross section of the porous, oil-absorbing flexible graphene / cellulose hybrid composite aerogel plugging material prepared in Example 2 of the present invention were fixed on a sample stage with conductive glue, sprayed with gold, and observed with a scanning electron microscope (SEM).

[0092] 3. The porous, oil-absorbing flexible graphene / cellulose hybrid composite aerogel plugging material prepared in Example 3 of the present invention was subjected to a contact angle test, wherein the medium was white oil.

[0093] 4. Take 10 mg of each of the porous, oil-absorbing flexible graphene / cellulose hybrid composite aerogel plugging material prepared in Example 2 of the present invention, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, and Comparative Example 5, and add them to 6 glass bottles containing 10 mL of white oil. The total mass of the glass bottles containing 10 ml of white oil is weighed and recorded, and placed in a water bath constant temperature oscillator (room temperature, 125 r·min -1 ) oscillate, and after reaching adsorption equilibrium, take out the aerogel adsorbed with white oil, weigh and record the current mass of the 6 glass bottles, and calculate the oil absorption rate of each.

[0094] 5. Carry out a series of plugging tests with different proportions to verify its effect in actual plugging application.

[0095] Micro-millimeter-scale formations will be simulated using artificial cores with fixed permeability and simulated fracture width of 500 μm.

[0096] The preparation formula of the oil-based drilling fluid is: 320mL white oil + 80mL 25wt% CaCl2 solution + 2wt% cyclohexanecarboxamide main emulsifier + 2wt% organic soil + 1wt% Span-80 auxiliary emulsifier + 2wt% CaO + API barite 85g + 2wt% 400 mesh ultrafine calcium carbonate + 3wt% 80 mesh ultrafine calcium carbonate + 3wt% filtration reducer. Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, and Comparative Example 5 are added to the prepared base slurry as plugging materials (the added amount is 3% of the total mass of the oil-based drilling fluid), and the permeability of the simulated formation before and after plugging is calculated to obtain the plugging rate of the simulated formation by different plugging materials, wherein the selection of organic soil meets the industry standard "Technical Specification for Organic Soil for Oil-Based Drilling Fluid" (Q / SY1817-2015).

[0097] Experimental Results

[0098] 1. By Figure 1aIt can be seen that the porous, oil-absorbing flexible graphene / cellulose hybrid composite aerogel plugging material prepared in Example 1 of the present invention has very dense pores. Figure 1b It can be seen that the composite aerogel plugging material can still maintain a certain shape after being pressed and bent. During the extrusion process, the aerogel did not completely collapse into debris due to the action of external force, and did not break during the bending process, indicating that the porous, oil-absorbing flexible graphene / cellulose hybrid composite aerogel plugging material prepared by the method of the present invention has a flexible effect.

[0099] 2. From Figure 2a to Figure 2d It can be seen that the porous, oil-absorbing flexible graphene / cellulose hybrid composite aerogel plugging material prepared in Example 2 contains a large number of dense micro-millimeter pores, which are formed by the accumulation of a large number of wrinkled and curved graphite sheets and cellulose grafting. The composite aerogel plugging material is formed by random overlapping and chemical cross-linking of graphene nano-mesh layers and cellulose mesh layers, presenting an interconnected three-dimensional spatial entangled network structure without agglomeration.

[0100] 3. From Figure 3 It can be seen that the contact angle of the porous, oil-absorbing flexible graphene / cellulose hybrid composite aerogel plugging material synthesized in Example 3 is 82° at 0s, and the contact angle rapidly decreases to 35° at 0.1s, and then drops to 26.6° at 0.15s, and finally drops to 19.7° at 0.2s, which indicates that the white oil is absorbed by the surface of the plugging material in a very short time of dripping and cannot stay on the surface of the synthetic material. This is due to the strong adsorption effect of the dense pores and the large specific surface area inside on the oil droplets after freezing pore formation, as well as the strong lipophilicity of the material as a whole.

[0101] 4. From Figure 4 It can be seen that the oil absorption rate of Example 2 of the present invention is higher than that of Comparative Examples 1-5.

[0102] 5. The following is the plugging rate after adding different materials

[0103] Table 1 Plugging rate of different plugging materials

[0104]

[0105] From Table 1, it can be seen that by comparing Comparative Examples 1 and 2 with the following Comparative Examples 3, 4, and 5; and Example 1, Example 2, and Example 3, it is not difficult to see that the reduced graphene oxide aerogel prepared by the hydrothermal reduction method is obviously not suitable for plugging micro-millimeter cracks, even if different types of reducing agents are used for reduction, because its own fragile structure is not sufficient to support the filling of the cracks; by comparing Comparative Examples 3, Comparative Examples 4, Comparative Examples 5 with Examples 1, Example 2, and Example 3, it can be seen that the hybrid cross-linking of the graphene three-dimensional network structure and the cellulose network has a certain effect on plugging, but the original stable structure may be destroyed due to the addition of other substances, resulting in a decrease in its pressure bearing capacity and plugging capacity.

[0106] From Example 1, Example 2, and Example 3, it can be seen that different amounts of raw materials have a considerable influence on the structural stability of the porous, oil-absorbing flexible graphene / cellulose hybrid composite aerosol, but all have very excellent plugging performance.

[0107] Table 2 Evaluation of the performance of drilling fluid on the amount of plugging material added

[0108]

[0109]

[0110] It can be seen from Table 2 that with the increase in the amount of porous, oil-absorbing flexible graphene / cellulose hybrid composite aerogel plugging material, the rheological properties and electrical stability of the oil-based drilling fluid system did not change significantly, indicating that the system was stable, but the high-temperature and high-pressure filtration loss was greatly reduced with the increase of plugging materials, indicating that the plugging materials cooperated with the rigid materials to form a dense plugging bridging network layer, which provided a strong force framework for the continued filling of the plugging materials. The two enhanced the plugging effect, reduced the filtration loss, and reduced the transfer of filtrate to the formation, and the plugging materials had good compatibility with the oil-based drilling fluid.

[0111] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.

[0112] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a graphene / cellulose hybrid composite aerogel plugging material, characterized in that: The following steps are involved: A. preparing graphene oxide powder into a graphene oxide dispersion, and heating and stirring to adjust the pH value to 4.5-8.5; B. Adding hydroxypropyl methylcellulose, polyvinyl alcohol, polyacrylamide and sodium borate solution to the graphene oxide dispersion treated in step A in sequence and at intervals to obtain a modified graphene dispersion; C. The modified graphene dispersion obtained in step B is heated, kept warm and dialyzed, and after the dialyzation, the dispersion is frozen and thawed at least twice, and then freeze-dried, and then thermally annealed in an inert atmosphere to obtain a graphene / cellulose hybrid composite aerogel plugging material.

2. The preparation method according to claim 1, characterized in that: In step A, the graphene oxide dispersion is prepared by the following method: dissolving graphene oxide powder in deionized water and performing ultrasonic dispersion to obtain the graphene oxide dispersion, and the heating temperature is 70° C. to 130° C.

3. The preparation method according to claim 2, characterized in that: In step A, the concentration of the graphene oxide dispersion is 5 mg / mL to 15 mg / mL.

4. The preparation method according to claim 1, characterized in that: In step B, the mass ratio of the hydroxypropyl methylcellulose to the graphene oxide powder in step A is 1:(0.5-1.5), the mass ratio of the hydroxypropyl methylcellulose to polyvinyl alcohol is (1.3-3.1):1, the mass ratio of the hydroxypropyl methylcellulose to polyacrylamide is (3-7):1, the mass fraction of the sodium borate solution is 1.5%-4.5%, and the mass volume ratio of the hydroxypropyl methylcellulose to the sodium borate solution is 1g / 1mL.

5. The preparation method according to claim 1, characterized in that: In step C, the heating temperature is 120° C. to 200° C., and the insulation time is 6 h to 12 h.

6. The preparation method according to claim 1, characterized in that: In step C, the dialysis time is 8 h to 14 h.

7. The preparation method according to claim 1, characterized in that: In step C, the freeze-drying time is 24 hours to 48 hours, the temperature is -30°C to -60°C, and the vacuum degree is 1Pa to 25Pa.

8. The preparation method according to claim 1, characterized in that: In step C, the thermal annealing treatment time is 0.1h~1h, the thermal annealing treatment temperature is 10℃~240℃, the heating rate is 1℃ / min~10℃ / min, the inert atmosphere is argon, and the argon intake rate is 5mL / min~20mL / min.

9. Use of the graphene / cellulose hybrid composite aerogel plugging material prepared by the preparation method according to claims 1 to 8 in plugging of oil-based drilling fluid.